Effect of growth regulators on growth, seed yield and quality attributes in garden pea (Pisum sativum var Hortense) cv. Pusa Pragati - SINGH, SUMEET KUMAR; TOMAR, B S; ANAND, ANJALI; KUMARI, SARITA; PRAKASH, KRISHNA (The Indian Journal of Agricultural Sciences, 2018)
The effect of foliar sprays of plant growth regulators (PGRs), viz. NAA (10, 15 and 20 ppm), GA3 (50, 75 and 100 ppm) and kinetin (10, 15 and 20 ppm) at 25 and 35 DAS was evaluated on growth, yield and seed quality attributes in garden pea (Pisum sativum var Hortense) cv. Pusa Pragati under field condition. Plant morphology was affected by spray of the three PGRs at vegetative stage. Plant height increased with increase in concentration of GA3 and kinetin, albeit NAA. However, GA3 did not influence the number of primary branches/plant, which were significantly increased by kinetin and NAA. GA3 had a profound effect on hastening the initiation of flowering by 3-5 days over water sprayed control, whereas other plant growth regulators did not affect the days to flowering. The seed quality parameters did not increase significantly on increasing the concentration of PGRs except seedling length and vigour index I. Application of GA3 led to best quality of harvested seed. Protein, N, P, Cu, Fe and Mn content of seeds increased with increase in concentration of kinetin and NAA. GA3 had no significant effect on nitrogen and crude protein content of seed but markedly increased K, Cu, Fe and Mn content. Maximum P content in seed was observed in plants sprayed with NAA. No significant change was observed in Zn content with either plant growth regulator.